KEANEKARAGAMAN ANGGREK TANAH DI KEBUN RAYA SAMARINDA - Aliri Aliri; Akas Pinaringan Sujalu; Maya Preva Biantary (Fakultas Kehutanan Universitas Mulawarman, 2018)
The study aims to identify the diversity of terrestrial orchids in the core zone botanical garden samarinda, using research Single Plot Method at 100x100m2. Data were collected using sample plots measuring 5 mx5 m. In the Core Zone of The Samarinda Botanical Garden found 705 clump of orchid composed of 5 species, most of the species Phaius tankervillie, Dipodium palodosum, Arachis flos-aeris, Cymbidium atropureum and Vandopsis lowii. Phaius tankervillie has highest an diversity index of species, dominanse index and sum of domanance ratio.